Determination Of Bod Kinetics Coefficient (K1) For The Leachate Less Than 5 Years From Pulau Burong Landfills - Kamaludin, Zulaikha (Universiti Sains Malaysia, 2006)
Rate of BOD degradation (k1) and the ultimate BOD (L0) are among the main parameters in biological treatment of wastewater, including leachate. These values are used for the design of aeration tank in activated sludge system, oxidation pond etc. Currently these values are not available for leachate. There are a few methods commonly used to determine k1 and Lo. These includes Least-square technique, Slope method, Moment method, Logarithmic method and Rhame`s method. The objectives of this study is to determine the rate constant, k1 and ultimate BOD, L0 values for semi aerobic leachate at Pulau Burong landfills. These values are very important and useful in the future for design leachate treatment plant with similar characteristic in Malaysia and overseas. Results indicated that the k1 values were in the range of 0.02349 day-1 to 0.1205 day-1 (Average = 0.0718 day-1) and L0 values 355.389 to 747 mg/L (Average = 495 mg/L) for Pond A. For pond B, the k1 values were in the range of 0.0236 to 0.110 day-1 (Average = 0.0743 day-1) and L0 329.27 to 707 mg/L (Average = 545 mg/L) respectively. Results indicated that for both ponds, the Slope method produced the lowest k1 value but the highest L0 value. In comparison, the Logarithmic method produced the highest k1 values for both ponds.